Cultural marginality among Asian women immigrants in Iceland : exploring the dimensions of cross-cultural adaptation and participation in social and educational settings - Cynthia Trililani 1974- (2015)
The impact of migration is a multicultural society. People are comparatively exposed to and are developing ideas of references to two or more cultural diversities. When people face the exposure to two or more cultures, issues of identity may present themselves as they possibly struggle with self-identity and varied cultural values. This could lead to cultural marginality, a feeling that one does not belong to any culture, but rather that one is ambivalent of both the values of the dominant host culture and the values of the culture of origin. Immigrant women who are sometimes considered as a minority group are vulnerable to the impact of cultural marginalization and discrimination. In addition, these women are susceptible to racism and stereotyping because of their gender, race and ethnicity (Bennett, 1993; Escrivá, 2000). The purpose of this research is to explore how the dimensions of cross-cultural adaptation influence Asian immigrant women in Iceland in constructing and developing their identity and how the concept of cultural marginality applies to them. Their participation in social and educational settings in Iceland is also examined. The participants consist of 6 Asian women immigrants from various countries in Southeast Asia who live in Iceland. Qualitative research with a phenomenological approach is employed in order to describe and understand the essence of lived experiences of individuals who have experienced a particular phenomenon. The data is collected individually with semi-structured interviews using open-ended questions throughout summer 2013 and spring 2014. The study reveals that all of the women are struggling to cope with distinctive cultural values and identity from the result of contact with different cultural values and attitudes. The dissimilarities of culture and lack of Icelandic language skills are the prominent factors in producing sociocultural and psychological barriers between the women and Icelandic society at large. The treatment they receive from the society, the apparent ...